Unlawful Acts According to Civil Law and Criminal Law - Aditya, Agung; Rakhmatika, Devi; Faradany Saputri, Nabila (The Digest: Journal of Jurisprudence and Legisprudence, 2023)
Land grabbing is not a new phenomenon and has occurred in Indonesia. The term "land grabbing" refers to the act of seizing rights or property arbitrarily, without adhering to laws and regulations, such as occupying land or houses that do not belong to the perpetrator. Unlawful land grabbing constitutes a legal violation and can be categorized as a criminal act. If the act is intentionally committed by someone who seizes the land of others, Article 167 of the Criminal Code (KUHPidana) may be applied. Meanwhile, the civil law aspects encompass Article 1365 and Article 1366, as in cases of land grabbing, there are parties who suffer losses and are entitled to compensation for the damages incurred.